Pengaruh Substitusi Tepung Jagung Terhadap Jumlah Total Mikroorganisme dan Daya Terima Pada Bolu Kukus - Anisa, Aulia Nurul, Dwi Sarbini, S.ST., M.Kes, Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Steamed sponge is a traditional food that favored people. The basic ingredients of steamed sponge are wheat flour. Efforts to reduce the use of wheat flour was by the use of local food such as corn. Corn has the advantage of containing vitamin A and vitamin E, has a low GI value, has a lower water content and could be made of flour. Corn flour was used as a substitute for wheat flour in making steamed sponge. The percentage difference substitutions would affect the total number of microorganisms and receptivity of steamed sponge. The purpose this study is to determine the effect of substitution of corn flour towards the total number of microorganisms and receptivity of steamed sponge. This research was an experimental research design by completely randomized design with factorial pattern. Variations of corn flour substitution are 0%, 10%, 20% and 30%. Effect of the data corn flour substitution on the total number of microorganisms and receptivity of tests were analyzed using Kruskal Wallis, real difference test receptivity using Duncan test with 95% confidence level. The results of research based on variations of substitution shows the highest of total number microorganisms steamed sponge with corn flour substitution of 10% (1,98x104 cfu / ml). The research results receptivity test based on color, aroma, flavor, texture, and the best of overall in substitution of 0%. Keywords: Corn flour, the total number of microorganisms, the receptivity, steamed sponge